Maternal Diet, Metabolic State, and Inflammatory Response Exert Unique and Long-Lasting Influences on Offspring Behavior in Non-Human Primates - Thompson, Jacqueline R.; Gustafsson, Hanna C.; DeCapo, Madison; Takahashi, Diana L.; Bagley, Jennifer L.; Dean, Tyler A.; Kievit, Paul; Fair, Damien A.; Sullivan, Elinor L. (Frontiers in Endocrinology, 2018)
Nutritional status influences brain health and gestational exposure to metabolic disorders, such as obesity and diabetes, increases the risk of neuropsychiatric disorders. The aim of the present study was to further investigate the role of maternal Western-style diet, metabolic state, and inflammatory factors in the programming of Japanese macaque offspring behavior. Utilizing structural equation modeling, we investigated the relationships between maternal diet, pre-pregnancy adiposity, third trimester insulin response, and plasma cytokine levels on 11-month-old offspring behavior. Maternal Western-style diet was associated with greater reactive and ritualized anxiety in the offspring. Maternal adiposity and third trimester macrophage-derived chemokine (MDC) exerted opposing effects on offspring high-energy outbursts. Elevated levels of this behavior were associated with low maternal MDC and increased pre-pregnancy adiposity. This is the first study to show that maternal MDC levels influence offspring behavior. We found no evidence suggesting maternal inflammatory response mediated the effect of maternal diet and metabolic state on aberrant offspring behavior. Additionally, the extent of maternal metabolic impairment differentially influenced chemokine response. Elevated pre-pregnancy adiposity suppressed third trimester chemokines, while obesity-induced insulin resistance augmented peripheral chemokine levels. Western-style diet also directly increased maternal interleukin (IL)-12. This is the first non-human primate study to delineate the effects of maternal diet and metabolic state on gestational inflammatory environment and subsequent offspring behavior. Our findings give insight to the complex mechanisms by which diet, metabolic state, and inflammation during pregnancy exert unique influences on offspring behavioral regulation.